Helicteres pegueroi (Malvaceae: Helicteroideae): A new species from the dry forests of the Dominican Republic - Martínez-Gordillo, Martha; Clase, Teodoro; Fragoso-Martínez, Itzi (Phytotaxa, 2020)
A new species of Helicteres from the Dominican Republic is described and illustrated; increasing the number of species occurring in the Caribbean to five. The new species, H. pegueroi, can be distinguished from H. jamaicensis and H. semitriloba by its habit and calyx and corolla colour, i.e. it is a shrub with red calyces and corollas; its pseudoactinomorphic flower due to a slight curvature at the base of the androgynophore; and its densely woolly, globose fruit. An artificial, dichotomous key is provided to distinguish the new species from the other species of the Caribbean region and Mexico.